Ethical Leadership and Employee Ethical Behavior: A Moderated Mediation Mechanisms - Rabie, Muhammad Osaid; Abdul Malek, Marlin (SEISENSE Journal of Management, 2020)
Purpose- Based on the ongoing unethical scandal in the organizations, this study aims to explain the relationship between ethical leaders and their followers’ ethical behavior by explaining the underlying mechanisms. Design/Methodology- Data were collected through a structured questionnaire from the employees working in companies that produce fast-moving consumer goods. Three hundred sixty-nine samples were taken to study the proposed relationships. Findings- Results showed ethical leaders positively influence followers. Perceptual and reflective moral attentiveness positively mediates between ethical leadership and ethical behavior of employees. Moral awareness negatively moderates between ethical leadership and followers’ ethical behavior via reflective moral attentiveness, whereas moral awareness does not moderate the relationship. Practical Implications- Following the call for determinants of ethical behavior, this study provides insights for the managers to foster ethical behavior at the workplace.